Effect of dough making parameters on the quality of pasta enriched with bran dietary fibers - Yurchak, Vera; Karpyk, Galina; Yukalo, Volodymyr (My University, 2013)
Organoleptic and cooking properties of pasta, also its physical and chemical quality factors have been determined. It has been established herewith that adding more bran leads to poor product tenacity and the amount of dry matter passing into cooking water increases. With moisture and kneading time increase the product tenacity improves, press productivity increases, and less of dry matter passes into cooking water. For the best quality the next parameters must be observed: bran dosage 20%, water temperature 60 ºC and kneading time must be 20 minutes.
Keywords: macaroni products; wheat bran; dough making; mathematical models; parameter optimization; макаронні вироби; пшеничні висівки; приготування тіста; математична модель; параметри оптимізації; макаронные изделия; пшеничные отруби; приготовление теста; математическая модель; параметры оптимизации; кафедра технології хлібопекарських і кондитерських виробів